1966
DOI: 10.1063/1.1707984
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Vacancies in MgO by Deformation

Abstract: Electron spin resonance and x-ray line broadening were used to measure the deformation-induced vacancies and dislocation densities, respectively, in MgO. The vacancy concentration was found to increase with increasing deformation rate and dislocation density. The generation of vacancies is explained by the nonconservative motion of dislocation jogs created by dislocation intersections in regions where the dislocation density is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The value of this charge depends on the different bonding energies of vacancies of negative and positive ions within a dislocation (Klein and Gager 1966;Tyapunina and Belozerova 1988). The value of this charge depends on the different bonding energies of vacancies of negative and positive ions within a dislocation (Klein and Gager 1966;Tyapunina and Belozerova 1988).…”
Section: Theory Of Shock Polarization Of Ionic Monocrystalsmentioning
confidence: 99%
“…The value of this charge depends on the different bonding energies of vacancies of negative and positive ions within a dislocation (Klein and Gager 1966;Tyapunina and Belozerova 1988). The value of this charge depends on the different bonding energies of vacancies of negative and positive ions within a dislocation (Klein and Gager 1966;Tyapunina and Belozerova 1988).…”
Section: Theory Of Shock Polarization Of Ionic Monocrystalsmentioning
confidence: 99%
“…For example, compression-induced plasticity in bulk MgO materials is related to the nucleation of dislocations, their movement, and intersections. 8 , 9 Enhanced deformation rates and dislocation densities in compressed bulk MgO samples seem to also promote ion vacancy formation 26 and triboemission of charge carriers. 27 Meanwhile, progress in experimental techniques has allowed for addressing plastic deformation and dislocation behavior of MgO at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically predicted energies of optical absorptions due to corners, edges, and (100) faces , were found to be in excellent agreement with the experimental values and have even enabled us to isolate spectral contributions from buried interfaces. , Moreover, photoexcitation studies revealed key insights into the energetics of charge separation and subsequent electron and hole trapping at surface defects. Structural deformation of MgO under loading is also relatively well-understood. For example, compression-induced plasticity in bulk MgO materials is related to the nucleation of dislocations, their movement, and intersections. , Enhanced deformation rates and dislocation densities in compressed bulk MgO samples seem to also promote ion vacancy formation and triboemission of charge carriers . Meanwhile, progress in experimental techniques has allowed for addressing plastic deformation and dislocation behavior of MgO at the nanoscale .…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of vacancies have been observed in crystalline metals during plastic flow (Klein and Gager, 1966;Seitz, 1952Seitz, , 1950. It has been pointed out that the average temperature increase due to energy dissipation of dislocation motion is probably not sufficiently high to increase vacancy and interstitial concentrations as a result of thermal effects alone (Seitz, 1952).…”
Section: Introductionmentioning
confidence: 99%